Photovoltatic Devices: Plasmonic Backscattering Effect in High‐Efficient Organic Photovoltaic Devices (Adv. Energy Mater. 2/2016). Issue 2 (20th January 2016) - Kakavelakis, George; Vangelidis, Ioannis; Heuer‐Jungemann, Amelie; Kanaras, Antonios G.; Lidorikis, Elefterios; Stratakis, Emmanuel; Kymakis, Emmanuel
Abstract : A new light trapping architecture to enhance the power conversion efficiency of organic photovoltaics is proposed and implemented. In article number 1501640, Emmanuel Kymakis and co‐workers demonstrate that the incorporation of gold nanorods inside the rear buffer layer, leads to the redistribution of photons inside the active medium mainly through efficient light back‐scattering, simultaneously increasing the exciton generation and charge collection.